Coasts in crisis a global challenge - Griggs, Gary B. (University of California Press, 2017)
"Almost half of the planet's population now lives in the coastal zone. The impacts of these people - three billion and rising - are increasingly affecting the most dynamic and constantly changing environments on Earth. All shorelines are also experiencing a rising sea level, which is causing coastal erosion and flooding, and what may be a more severe future storm and wave climate. Future sea-level rise may be the greatest challenge human civilization has ever faced. Dense populations are taking a toll on the coastal zone, impacting not only the shoreline itself, but also the nearshore waters. The myriad effects include industrial, agricultural, and domestic runoff and discharge; the disposal and accumulation of plastic and other marine debris; extraction of groundwater and petroleum leading to sea water intrusion and ground subsidence; large port developments with their thousands of ships and their associated impacts; overfishing and loss of habitats; and impacts of dams, sand mining, and coastal engineering structures on sandy beaches. Individual hazards, risks, and issues have been studied and written about individually, but there is no reference, book, or source until this one that treats the entire coastal zone as a region under threat. While there are more examples included from California and the United States, the book covers issues and environments from a global perspective so that this book will be useful and informative for students or readers anywhere on the planet."--Provided by publisher.